Early Childhood Education Management as an Effort to Improve the Quality of Learning - Muh. Ibnu sholeh (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2025)
Early childhood education management plays a strategic role in improving the quality of learning in Early Childhood Education (ECE) institutions. Learning quality is not determined solely by teacher competence but also by how educational processes are systematically and sustainably managed. This study aims to examine early childhood education management as an effort to enhance learning quality. The research employed a qualitative approach using a library research design. Data were collected through a review of books, scholarly journal articles, previous research findings, and policy documents relevant to ECE management. Data collection was conducted through documentation studies, while data analysis employed content analysis techniques. The findings indicate that the implementation of educational management encompassing planning, organizing, implementation, and evaluation of learning significantly contributes to improving the quality of early childhood learning. Effective educational management is able to create learning experiences that are well-directed, enjoyable, and aligned with children’s developmental needs.